PROFIL FITOKIMIA DAN AKTIFITAS ANTIACETYLCHOLINESTERASE DARI DAUN TABAT BARITO (Ficus Deltoidea Jack) - Suryatir -; Hazli Nurdin; Dachriyanus - (Jurnal Riset Kimia, 2009)
ABSTRACT Phytochemical study and antiacetylcholinesterase assay by using bioautography method were carried out on polar fraction of tabat barito (Ficus deltoidea jack) leaves. The result of this studies showed that the leaves contained flavonoid, terpenoid, steroid and fenolic compounds. This extract gave positive result on antiacetylcholinesterase. Keywords: Antiacetylcholinesterase, Ficus deltoidea Jack